Refracture of osteoporotic vertebral body after treatment by balloon kyphoplasty: Three cases report. Issue 49 (December 2017) - Li, Xigong; Lu, Yang; Lin, Xiangjin
Abstract: Rationale: Balloon kyphoplasty is a widely accepted treatment of osteoporotic vertebral compression fractures (OVCFs) with good results and a low risk for complications. A refracture of previously treated vertebra is a relatively rare condition. Patient concerns: We reported our 3 cases and reviewed all relevant literatures of 11 cases with refracture of osteoporotic vertebral body after kyphoplasty. Diagnoses: Follow-up radiographs or magnetic resonance imaging examination confirmed refractures of previously treated vertebrae after kyphoplasty. Interventions: One patient with 1 refracture of osteoporotic vertebral body after kyphoplasty was treated conservatively, but the other 2 patients were treated surgically because of multiple vertebral fractures or neurological deficits. Outcomes: The average age of the patients was 76.8 years (range, 63–86 years). All the patients had severe osteoporosis with a mean T-score of −3.46 (range −5.0 to −3.0). The sites of refractures are in the lumbar and thoracolumbar regions. Severe osteoporosis, the presence of intravertebral cleft, and a solid lump injection pattern of polymethylmethacrylate would result in insufficient strengthening effects of cement augmentation and therefore increased the likelihood of refractures of the kyphoplasty vertibrae. Lessons: Patients with OVCFs and intravertebral cleft who did not obtain complete pain-relief at the treated vertebral level after kyphoplasty should be strictly followed up. Early finding of this condition and rapid intervention might contribute to avoiding the occurrence of the cemented vertebral refracture after kyphoplasty. Conservative treatments such as back brace and antiosteoporotic medications were strongly recommended.